Strategic Transformation Toward World-Class University: The Quacquarelli Symonds (QS) Ranking System Implementation at a Public University in South Kalimantan - Mutiani Mutiani; Rifiana Rifiana; Nurmelati Septiana; Rizky Amelia; Fadloe Robby (The Kalimantan Social Studies Journal, 2026)
The global higher education landscape demands universities to continuously enhance their competitiveness through systematic quality improvement and international recognition. A regional Indonesian university (hereinafter referred to as "the Institution") has demonstrated significant progress in national and regional rankings, positioning itself strategically for global recognition. This study examines the Institution's strategic policy framework for achieving world-class university status through the implementation of the Quacquarelli Symonds (QS) ranking system, targeting entry into the top 1,500 universities globally by 2027. A comprehensive policy analysis approach was employed, examining institutional strengths, strategic imperatives, and performance indicators. The study synthesizes data from national rankings (Edurank 2025, AD Scientific Index 2025) and institutional metrics, incorporating the QS ranking methodology framework. Results of the research, the Institution has achieved notable rankings including 27th nationally, 532nd in Asia, and 1802nd internationally (Edurank 2025), with recognition among 15 leading institutions nationally (AD Scientific Index 2025) and consistent top ranking in its provincial region. Three strategic pillars have been identified: World Class Research (targeting 800 Scopus/WoS publications annually), Internationalization (targeting 6 10% international students), and Global Reputation (targeting QS reputation score of 45%). The strategic transformation framework, grounded in regional competitiveness, talent quality, research impact, national reputation, and international investment, provides a robust pathway for the Institution's advancement. Implementation requires systematic monitoring through KPI frameworks, real-time dashboards, and accountability mechanisms incorporating process, output, outcome, and impact